Fostering environmental awareness through ecological art to enhance creativity in primary school students - Karsono, Karsono; Firdani, Lusiana; Yahya, Ayyas; Wiranegara, Haffa Islam Mubarok (Universitas Ahmad Dahlan, 2024)
The escalating environmental challenges, such as climate change and biodiversity loss, highlight the urgent need for education systems to foster environmental awareness and action in younger generations. This study investigates the integration of Ecological Art into the Pancasila Student Profile Strengthening Project (P5) in two Indonesian primary schools in contrasting ecological settings: a mountainous region and a coastal area. Employing a qualitative approach, the research examines how local ecological contexts influence students’ creativity, environmental awareness, and collaboration. Data were collected through observations, interviews, and document analysis to evaluate the role of Ecological Art in addressing local and global ecological concerns. Findings demonstrate that using natural materials such as bamboo and clay in the mountainous school reinforced connections to cultural heritage and sustainability. Conversely, the coastal school’s focus on recycling plastic waste underscored the urgency of combating pollution. Ecological art engages students emotionally and socially, fostering environmental consciousness and creative problem-solving skills. However, limited resources and insufficient teacher training were identified as barriers to broader implementation. This research highlights the potential of Ecological Art as a pedagogical tool to enhance sustainability education through place-based learning and community engagement. Recommendations are provided for educators and policymakers to adapt curricula to local ecological and cultural contexts, contributing to the broader discourse on transformative education for sustainability.